2021
DOI: 10.1097/mbc.0000000000001019
|View full text |Cite
|
Sign up to set email alerts
|

Challenges and concerns of patients with congenital bleeding disorders affected by coronavirus disease 2019

Abstract: Coronavirus disease 2019 (COVID-19) is a new medical challenge for all individuals, especially for those with underlying disorders, such as congenital bleeding disorders (CBDs). Therefore, the pandemic might significantly change the behaviour of patients with CBDs and results in some challenges. In the present study, we assessed the main challenges of COVID-19 infection to patients with CBDs. Data were collected from medical files and interviews of patients with CBDs who had COVID-19 infection. Follow-ups were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…Studies have shown that the COVID-19 pandemic had a negative impact on lifestyle behaviors, routine care, and replacement therapies in patients with CBD [15][16][17][18]. However, there are only a limited number of clinical studies that have investigated the outcomes of COVID-19 in patients with bleeding disorders, and it is not known whether patients with bleeding disorders are more or less prone to the severe form of infection.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that the COVID-19 pandemic had a negative impact on lifestyle behaviors, routine care, and replacement therapies in patients with CBD [15][16][17][18]. However, there are only a limited number of clinical studies that have investigated the outcomes of COVID-19 in patients with bleeding disorders, and it is not known whether patients with bleeding disorders are more or less prone to the severe form of infection.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to these concerns and complications, the impact of COVID-19 on the hemostasis system has presented further challenges for both patients and their health care providers. 5 6 7…”
mentioning
confidence: 99%
“…3,4 In addition to the wellknown risk factors, some studies have also examined the impact of COVID-19 on patients with congenital bleeding disorders (CBDs). [5][6][7][8] The pandemic has affected the lives of patients with CBDs more severely than those of the general population. 5 Similar to patients with other chronic diseases such as cancer, diabetes mellitus, thalassemia, and others, most patients with CBDs assume that they are at a higher risk of severe COVID-19 outcomes compared with healthy individuals.…”
mentioning
confidence: 99%
“…The authors state that COVID‐19 infection has great consequences on the lives of patients with CBDs and caused abandonment of their treatment. 8 …”
mentioning
confidence: 99%
“…The authors state that COVID-19 infection has great consequences on the lives of patients with CBDs and caused abandonment of their treatment. 8 A study, as presented at the EAHAD congress in 2021, 9 was carried out with PWH (N = 45) and healthcare professionals (N = 24) in the Czech Republic and United Kingdom. They responded to 24 questions.…”
mentioning
confidence: 99%